Fear and Favoritism in the Time of COVID-19 - Han, Baran; Ho, Benjamin; Rhee, Inbok; Tabakis, Chrysostomos (KDI School of Public Policy and Management, 2021)
Does fear cause us to "circle the wagons" and favor those in our in-group? Or does fear of the \other" cause us to recognize our common humanity and become more charitable to those we might otherwise consider outsiders? The measurement of this effect is confounded by the fact that some groups respond more strongly to fear than others. We run an online experiment on a nationally representative sample in South Korea in which we induce fear via the autobiographical emotional memory task method and examine the impact on donations to either an in-group charity (the Korean Red Cross) or one that caters to an out-group (the Korea Support Center for Foreign Workers). We find that, while the reported level of fear is negatively correlated with donations to the out-group, the induced fear caused by the experimental intervention is positively correlated with donations to the out-group. We also find that the fear effect depends on political views, media exposure, and social preferences. We conrm our experimental results by looking at how regional attitudes toward out-groups have shifted over time and compare those changes to the average level of reported fear during the COVID-19 pandemic. Places that report the most fear of COVID-19 also have had the greatest increases in prosocial attitudes toward out-groups.
Keywords: Fear; COVID-19; In-group Favoritism; Out-group Bias